Asymmetric Trading Costs Prior to Earnings Announcements: Implications for Price Discovery and Returns - JOHNSON, TRAVIS L.; SO, ERIC C. (Journal of Accounting Research, 2018)
ABSTRACT We show that the cost of trading on negative news, relative to positive news, increases before earnings announcements. Our evidence suggests that this asymmetry is due to financial intermediaries reducing their exposure to announcement risks by providing liquidity asymmetrically. This asymmetry creates a predictable upward bias in prices that increases preannouncement, and subsequently reverses, confounding short‐window announcement returns as measures of earnings news and risk premia. These findings provide an alternative explanation for asymmetric return reactions to firms' earnings news, and help explain puzzling prior evidence that announcement risk premia precede the actual announcements. Our study informs methods for research centering on earnings announcements and offers a possible explanation for patterns in returns around anticipated periods of heightened inventory risks, including alternative firm‐level, industry‐level, and macroeconomic information events.